Modern Business Statistics, with Microsoft Office Excel - Anderson, David Ray, 1941-, author 380358; Sweeney, Dennis J., author 380374; Williams, Thomas Arthur, 1944-, author 380378 (Mason, OH : South-Western Cengage Learning, 2012)
Give your students a balanced, conceptual understanding of statistics with a focus on real-world applications and the integrated strengths of Microsoft Excel 2010. The authoritative leader in modern business statistics, this best-selling comprehensive text carefully discusses and clearly develops each statistical technique in an application setting. Microsoft Excel 2010 instruction, integrated in each chapter, plays an integral part in strengthening this edition's applications orientation. Immediately after each easy-to-follow presentation of a statistical procedure, a subsection discusses how to use Excel to perform the procedure. This integrated approach emphasizes the applications of Excel while maintaining a primary focus on the statistical methodology. Step-by-step instructions and screen captures further clarify student learning. A wealth of timely business examples, proven methods, and additional exercises throughout this edition demonstrate how statistical results provide insights into business decisions and present solutions to contemporary business problems. High-quality problems noted for their unwavering accuracy and the authors' signature problem-scenario approach clearly show how to apply statistical methods in practical business situations. New case problems and self-tests allow students to challenge their personal understanding. This edition's comprehensive support package, including the CengageNOW course management system, provides everything you and your students need for an understanding of business statistics. Anderson/Sweeney/Williams' MODERN BUSINESS STATISTICS, 4e, is SIMPLY EXCELLENT! The Student Essential Site PAC (Printed Access Card) that comes with the new book includes: Case Files, Example Files, Problem Files, Tutorials, Solvertable, Palisade DecisionTools (StatTools), Excel Tutorial.